2009
DOI: 10.1021/om900674y
|View full text |Cite
|
Sign up to set email alerts
|

DFT-Based Explanation of the Effect of Simple Anionic Ligands on the Regioselectivity of the Heck Arylation of Acrolein Acetals

Abstract: The Heck arylation of acrolein acetal has been studied computationally and compared to the corresponding reaction with allyl ethers. The reaction can be controlled to give either cinnamaldehydes or arylpropanoic esters by addition of different coordinating anions, acetate, or chloride. The computational study reveals that coordinating acetate raises the energy of an intermediate sufficiently to block the access to an otherwise favorable β-hydride elimination. The reaction path is also compared to that of allyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The activated complex that occurs during a -hydride elimination exhibits some charge separation as bonds form and break, which like migratory insertion is consistent with the observation that dipolar solvents accelerate the reaction (Scheme 40). 223,224,225 226 However, on some occasions less polar electron donors give superior yields, e.g. ethers (Scheme 42).…”
Section: Heck Reactionmentioning
confidence: 99%
“…The activated complex that occurs during a -hydride elimination exhibits some charge separation as bonds form and break, which like migratory insertion is consistent with the observation that dipolar solvents accelerate the reaction (Scheme 40). 223,224,225 226 However, on some occasions less polar electron donors give superior yields, e.g. ethers (Scheme 42).…”
Section: Heck Reactionmentioning
confidence: 99%
“… 19 , 20 , 42 44 In addition, the β-hydride elimination step that is an important feature of the current reaction has also been investigated. 30 , 31 For asymmetric Heck reactions, previous studies have focused on cyclic substrates. 32 , 45 However, to our knowledge, the more complex situation, where asymmetry is induced in an open-chain alkene, has not been studied theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is necessary to investigate all possible TSs generating linear or branched product, irrespective of the energies of the initial complexes. [42] It will be shown that the crossover between opposite regiochemical preferences on the two major paths is a general phenomenon observed for all four P ligands. The selectivity is determined mainly by the Gibbs free-energy difference DG°between the two lowest TS giving linear and branched product, respectively.…”
Section: Resultsmentioning
confidence: 89%
“…However, along the reaction coordinate the energy curves of the different paths may cross and the relative energies for the different coordination modes will be interchanged. Thus, it is necessary to investigate all possible TSs generating linear or branched product, irrespective of the energies of the initial complexes 42. It will be shown that the crossover between opposite regiochemical preferences on the two major paths is a general phenomenon observed for all four P ligands.…”
Section: Resultsmentioning
confidence: 99%